A identidade de fã mediada pelos fanzines: análise do discurso de fã nos fanzines brasileiros de histórias em quadrinhos na década de 1990 - Medeiros, Lucas de Sousa (2016)
Fan identity is not a fixed construction, but a continuous process of relationship between the fan itself with his object of fannish behavior, other fans of the same object, and his only desires and aspirations. It‟s is constructed as an performance and not as an essence, being the result of all his fan practices, practices that does not happens in an social void, but inside deterritorialized communities made of people with the same fan interests. The brazilian comic fandom, that exists within a complex market, dominated by foreign productions e limited for domestic production, found in the fanzines its main media. Made, edited, published and distributed by fans themselves, fanzines was exchanged between fans in Brazil and abroad, becoming an communication network that cross thoroughly the brazilian comic book fandom. Through the fanzines the fans conducted a public debate about comic books in Brazil, it fans and their function within the fandom. Relating their subjective experiences to the discussions held, the comic fans had constructed their identities in conformity with the expectative of their fandom.